Colémbolos (Hexapoda, Collembola) asociados con carpóforos de basidiomicetes recolectados en el SW de Cataluña - Mateos Frías, Eduardo; López, R.; Barranco, T.; Hoyo Navarro, Pilar; Llimona i Pagès, Xavier (Revista Catalana de Micologia, 2007)
Collembola (Hexapoda, Collembola) associated with Basidiomycetes sporocarps in SW Catalonia. We have studied the collembola species found in basidiomata of 41 different species of fungi belonging to the Class Basidiomycetes, collected in several districts of the mediterranean SW Catalonia. We have found 5575 individuals of collembola of nine different species. Ceratophysella tergilobata represents the 99,8% of the total individuals and is present in the 94,8% of analysed basidiomata. In consequence this species must be considered an habitual inhabitant of the basidiomata of the mediterranean districts of Catalonia. The examination of the gut content of the studied col1embola reveals that their relationship with the basidiomata is of nutritional type.